Характер питания лисицы в зоне высокой численности ондатры (Колымо-Индигирская низменность) - Ревин, Ю.В. (Вестник зоологии, 1976)
Analysis of 636 samples of excrements of Vulpes vulpes L. made it possible to determine its food assortment in the basin of the middle Kolyma river as well as changes in the feed according to seasons and years (1966-1972). Ondatra zibethica L., the acclimatized rodent, is the main food object (64.3% of occurence). Lepus tinzidus- L., a group of the Microtinae subfamily species and Lagopus lagopus L. amount to 15.6, 29.8 and 5.4% respectively of the food composition. Species-aborigines even in the years of their abundance are eaten by the fox to less extent, that is why they are significant only as an accessory food.